Enhancing Internal Factors Unlocks Profit in Saudi Banks: Meningkatkan Faktor Internal Membuka Laba di Bank-bank Arab Saudi - Asmaa Abdul rida Daghir; Omar Mohammed Habeeb; Yasir Jihad Saeed (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Banks' profitability is crucial for financial stability and economic growth. Specific Background: Internal factors such as capital adequacy, asset quality, and management effectiveness play a significant role in determining profitability. However, the impact of these variables on Saudi banks needs further exploration. Knowledge Gap: Existing research lacks a comprehensive analysis of how these internal variables affect the profitability of Saudi banks over a long period. Aims: This study examines the effect of changes in capital adequacy, asset quality, management effectiveness, and liquidity on the bank profit index, measured by the return on assets (ROA) at Saudi Fransi Bank from 2000 to 2022. Results: Quantitative analysis reveals that capital adequacy and asset quality have a significant positive impact on ROA, with 1% increases in each leading to 20% and 76% increases in ROA, respectively. In contrast, increased liquidity and management inefficiency negatively affect ROA, decreasing it by 33% and a significant margin, respectively. The internal variables account for about 96.4% of the variation in profitability. Novelty: This study offers a detailed long-term analysis of internal factors affecting bank profitability in Saudi Arabia. Implications: Enhancing asset quality and management effectiveness is crucial for improving profitability and reducing costs, benefiting both Banque Saudi Fransi and the broader banking sector. Highlights: Positive Impact: Capital adequacy and asset quality enhance bank profitability. Negative Impact: Higher liquidity and management inefficiency reduce profitability. High Explanatory Power: Internal variables explain 96.4% of profitability variation. Keywords: Bank Profitability, Return on Assets, Capital Adequacy, Asset Quality, Management Effectiveness